WHY WERE PRESERVICE ENGLISH TEACHERS RELUCTANT TO SPEAK ENGLISH? Case in IKIP PGRI Pontianak - Dedi Irwan; Faryah Anshariyah; Maliqul Hafis (Institut Pendidikan Tapanuli Selatan, 2021)
This research aimed to find out factors affecting the reluctance of preservice English teachers who were studying in English Education Study Program of IKIP PGRI Pontianak to speak English. Descriptive research with quantitative approach was applied in this research. To collect the data, online questionnaire through google form was adopted. Sixty-five preservice English teachers were involved in the data collection process. The finding of this research showed three factors affecting preservice English teachers’ reluctance to speak English, namely linguistic factor, sociocultural factor and psychological factor. Furthermore, correlation analysis found out that there were no significant correlation between preservice teachers’ responses regarding the factor affecting their reluctance to speak English.